Efficient single-mode GaAs/AlGaAs W waveguide phase modulator with a low propagation loss - Byun, YT; Park, KH; Kim, SH; Choi, SS; Yi, JC; Lim, TK (OPTICAL SOC AMER, 1998)
We report a single-mode P-P-p-i-n-N-N GaAs/AlGaAs W waveguide phase modulator with a high phase modulation efficiency and a low propagation loss. The phase modulator with a W-shaped refractive-index profile utilizes a novel epilayer structure to reduce the propagation loss associated with doped layers and to obtain a phase modulation efficiency larger than those of P-i-N double heterostructure modulators. The phase shift and propagation loss were measured with a Fabry-Perot resonance method at 1.31-mu m wavelength. A phase modulation efficiency as high as 34.6 degrees/V mm was measured for TE polarized light. Also propagation losses of less than 0.6 dB/cm were achieved. As a result, the W waveguide phase modulator that exhibits a high phase modulation efficiency and a low propagation loss have been experimentally realized for the first time as far as we know. (C) 1998 optical Society of America.
Keywords: 1.3 MU-M; WAVE-GUIDE; DOUBLE HETEROSTRUCTURES; DEPENDENCE